Mediation Analysis of the Effect of Visuospatial Memory on Motor Skill Learning in Older Adults. Issue 1 (2nd January 2023) - Hooyman, Andrew; Lingo VanGilder, Jennapher; Schaefer, Sydney Y.
Abstract: There is high inter-individual variability in motor skill learning among older adults. Identifying the nature of these individual differences remains challenging due to interactions between participant characteristics (e.g., age, cognition) and task-related factors (e.g., nature of task, level of skill pre-training), making it difficult to determine plausibly causal relationships. This study addresses these competing explanations by using mediation analysis to examine plausible causal inference between visuospatial memory and one-month retention of both gross and fine motor components of a functional upper-extremity task following training. Results suggest that better visuospatial memory results in more retention of fine but not gross motor skill, expanding on previous correlational studies in older adults and informing future interventions for maximizing motor learning in geriatric populations.